Interactivity in Cybermedia News: An Interview with Journalists in Colombia, Peru, and Ecuador - Barredo Ibáñez, Daniel (2019)
Interactivity is a factor on which cyber journalism is based and summarizes participation options between a user and the medium, a user with other users, and a user with editors. In this study, we focus on the latter in three countries-Colombia, Peru, and Ecuador-, which have been identified owing to their technological gap and the emerging importance of online communication for their respective societies. Through 35 in-depth interviews with journalists from these countries, we analyzed the concept of interactivity of these professionals and their relationship with users. The results revealed that the journalists positively valued civic contributions as a space for diagnosis, although they do not perceive its informational value, as they relate them to the context of opinions. These results verify the prevalence of journalism as strongly influenced by conventional offline production routines.